Aberrant right hepatic artery in pancreaticoduodenectomy for adenocarcinoma: impact on resectability and postoperative outcomes. Issue 3 (19th June 2013) - Kim, Peter T. W.; Temple, Sara; Atenafu, Eshetu G.; Cleary, Sean P.; Moulton, Carol‐Anne; McGilvray, Ian D.; Gallinger, Steven; Greig, Paul D.; Wei, Alice C.
Abstract Objectives An aberrant right hepatic artery (aRHA) may pose technical and oncologic challenges during pancreaticoduodenectomy (PD) for pancreatic adenocarcinoma (PA) as a result of its proximity to the head of the pancreas. The aim of this study was to assess the impact of an aRHA on resectability, and perioperative and oncologic outcomes after PD for PA. Methods An 11‐year retrospective cohort study was conducted. A total of 289 patients with PA scheduled for PD with intent for resection were included in the study. Results Of 289 patients, 249 underwent PD and 40 were found to have unresectable tumours. Incidences of aRHA in the resectable (14.9%) and unresectable (7.5%) groups were similar (P = 0.2); the main reasons for aborting PD were not directly related to the presence of an aRHA. In patients who underwent resection, complications occurred more frequently in the standard PD group (41.5% versus 24.3%; P = 0.04), but there was no difference in rates of positive margin (R1) resection (10.8% versus 16.0%; P = 0.4) or median overall survival (17 months versus 23 months; P = 0.1) between patients with and without an aRHA. Conclusions The presence of an aRHA in patients with PA does not affect resectability. In patients with resectable tumours, the presence of an aRHA does not increase morbidity or R1 resection rates and does not impact on overall survival.